Teknologi Pertanian Alat Penyiang Gulma Untuk Mendukung Kemandirian Teknologi Pertanian Di Dusun Duhuh I, Desa Demen, Kecamatan Temon, Kabupaten Kulon Progo, Yogyakarta - Bagus Prasetiyo, Angger; Rizqi Prastowo, (ReTII, 2022)
Kelompok Usaha Peningkatan Pendapatan Keluarga Sejahtera in Dukuh I, Demen, Temon, Kulon Progo. This UPPKS group consists of approximately ten people whose livelihoods are farmers. Meanwhile, the business units of the UPPKS group are catering and agriculture. This community service activity aims to overcome problems and help groups in handling rice plants. From the initial results of the service team on agricultural land, there were several problems faced by the UPPKS Group. The problem farmers face is that weeding weeds into wild plants is one of the threats to rice plants for the growth and development of rice plants. Usually, farmers overcome this problem with these weeds manually. This activity requires a lot of energy and a long time, and farmers use no machines to deal with weed problems. The implementation method is problem-solving, mentoring, monitoring, and evaluation. The service team makes innovations for weed control devices using machines through this service. The science and technology offered in this activity is a rice weeding machine. The solution provided is to design and manufacture weed weeding machines and provide training and assistance on using and maintaining effective weeding devices. The results of this PKM obtained one unit of rice weeding machine and increased skills in the use and maintenance of rice weeding machines in the UPPKS Group Dusun Dukuh I, Demen, Temon, Kulon Progo